2001
DOI: 10.1017/s0022112000002147
|View full text |Cite
|
Sign up to set email alerts
|

Leading-edge receptivity of a hypersonic boundary layer on a flat plate

Abstract: Experimental investigations of the boundary layer receptivity, on the sharp leading edge of a flat plate, to acoustic waves induced by two-dimensional and threedimensional perturbers, have been performed for a free-stream Mach number M ∞ = 5.92. The fields of controlled free-stream disturbances were studied. It was shown that two-dimensional and three-dimensional perturbers radiate acoustic waves and that these perturbers present a set of harmonic motionless sources and moving sources with constant amplitude. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 20 publications
6
105
0
Order By: Relevance
“…For the flow over the flat plate, three sets of grid structures are used to check the grid independence of numerical simulation results near the leading edge. The steady flow is compared with the experimental measurements of Maslov et al [29]. At three different locations, x 96, 121, and 138 mm (R 1134:46, 1254.19, and 1329.66); the distributions of the dimensionless streamwise velocity and normalized Mach number in the wall-normal direction are in good agreement with those measured in experiments.…”
Section: Direct Numerical Simulation Approachsupporting
confidence: 58%
“…For the flow over the flat plate, three sets of grid structures are used to check the grid independence of numerical simulation results near the leading edge. The steady flow is compared with the experimental measurements of Maslov et al [29]. At three different locations, x 96, 121, and 138 mm (R 1134:46, 1254.19, and 1329.66); the distributions of the dimensionless streamwise velocity and normalized Mach number in the wall-normal direction are in good agreement with those measured in experiments.…”
Section: Direct Numerical Simulation Approachsupporting
confidence: 58%
“…Fast modes do undergo decay and hence the receptivity to fast sound waves should be relatively weaker. Fedorov (2003) made detailed comparison with the experimental data of Maslov et al (2001) and observed reasonably good agreement for planar or moderately three-dimensional disturbances, but the prediction deteriorates and even exhibits opposite trends when three-dimensionality becomes sufficiently strong. Indeed, highly oblique instability modes with spanwise wavenumbers β > √ M 2 − 1 α have phase speeds much smaller than the free-stream velocity and acquire a triple-deck structure (Smith 1989), where α is the streamwise wavenumber.…”
Section: Introductionmentioning
confidence: 92%
“…All these observations testify the crucial role of receptivity. However, there have been just a few detailed measurements of receptivity using controlled free-stream disturbances, and these were conducted by Maslov et al (2001) and Semionov & Kosinov (1999, 2008 for flat plates with sharp and blunt leading edges.…”
Section: Introductionmentioning
confidence: 99%
“…It reveals the physics of local receptivity associated with diffraction and scattering of acoustic waves near the leading edge of the plate. In [4], these theoretical results are compared with the experimental data [5] and numerical calculations [6].…”
Section: Introductionmentioning
confidence: 99%
“…The angles of inclination of 0 and ± 45 ° with respect to the plate are considered. In [13], the results for these angles were compared with the results of the asymptotic theory [5,6]. In [14], calculations of the receptivity of the boundary layer to fast and slow acoustic waves at M=4.5.…”
Section: Introductionmentioning
confidence: 99%